Biogeographic Variation Analysis of Phenotypic and Nutritional Quality Traits of Cultured Conger myriaster Along the Yellow Sea Coast of China - Yan Chen; Meijun Tao; Bao Shi; Shenglei Han; Binghua Liu; Lianshun Wang; Kewen Yan; Xinyu Zhao; Mingze Liu (Fishes)
Aquaculture has become increasingly important as a source of high-quality animal protein and fatty acids for humans. This study investigated the morphological traits, general nutritional component, amino acid composition, fatty acid composition, and antioxidant enzyme activity of artificially cultured whitespotted conger Conger myriaster from three different suppliers, Haiyang Yellow Sea Fisheries Co., Ltd. (YT), Rizhao Rongwang aquatic science and technology Co., Ltd. (RZ), and Weihai Shenghang aquatic science and technology Co., Ltd. (WH), based on the Yellow Sea coast in China. Of the 19 morphological traits, total length, body length, and vertical eye diameter were significantly different in the C. myriaster of YT, RZ, and WH (p < 0.05). The hepatosomatic index (HSI) of YT was significantly lower than that of RZ and WH (p < 0.05), and the gonadosomatic index (GSI) was not significantly different. The moisture, crude lipid, and crude ash contents in YT were significantly different from those in RZ and WH (p < 0.05). The methionine (Met) of RZ was significantly higher than that of YT and WH (p < 0.05). C. myriaster from YT, RZ, and WH were detected to have 26, 27, and 26 fatty acids, respectively. The docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) contents of YT were significantly higher than those of RZ and WH (p < 0.05). There were no significant differences in the antioxidant enzyme activities of C. myriaster from YT, RZ and WH (p > 0.05). The results showed that there are differences in the morphological traits, general nutritional component proximate composition, and amino acid and fatty acid compositions of cultured C. myriaster from different regions.